The relevance of livestock husbandry in the context of food security: a bibliometric outlook of research studies from 1938 to 2020 - Idamokoro, Emrobowansan Monday (Frontiers in Sustainable Food Systems, 2023)
The present study aimed to report knowledge-based outcomes on global studies of livestock farming as a tool to address food security, while considering the recurring problems caused by malnutrition and hunger among vulnerable persons, especially in developing countries. A total of 2,012 scientific peer-reviewed studies were retrieved in BibTeX design for analysis using bibliometric collections in R studio software. The results obtained from the software included among others, authors, keywords plus, citations, collaborations, affiliations, journals, countries impact and key words. Published peer-reviewed discoveries on livestock husbandry as related to food security gathered from Scopus and the Web of Science (WOS) databanks were used, with a yearly rise in knowledge-based research of 15.04% during the timespan of the investigation. The results of the investigation revealed that the United States was ranked first with an aggregate of 236 publications [including Single Country Publications (SCP) = 225 and Multiple Country Publications (MCP) = 11] and had a huge international scientific effect with the highest article citations (n = 9,138). The most frequently used authors’ keywords in the present research niche area were food security (n = 475), livestock (n = 123), agriculture (n = 100), climate change (n = 99), sustainability (n = 55), cattle (n = 40), and nutrition (n = 37), which gave a clear direction for the related research studies regarding how livestock production can be used to enhance food security. The study in consideration presented an international picture that addresses the pool of knowledge-based, peer-reviewed findings of livestock production research and its significance to food security, while providing a clue regarding further investigations in this research niche area. It is of high essence to emphasise that the current findings solely focused on prime areas of livestock production as related to food security research; thus, it is anticipated that novel empirical research work and potential scientific findings will provide novel understanding and precision to livestock husbandry as a possible instrument to tackle the challenges of food security as new discoveries emerges.